Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/glia.22272
|View full text |Cite
|
Sign up to set email alerts
|

S1P1 receptor subtype inhibits demyelination and regulates chemokine release in cerebellar slice cultures

Abstract: Sphingosine-1-phosphate receptors (S1PRs) are drug targets for the compound FTY720, which is the first oral therapy developed for treatment of relapsing-remitting multiple sclerosis. S1PRs play a variety of functional roles in the differentiation, proliferation, survival and/or migration of neurons and glia. In this study, rat organotypic cerebellar slice cultures were used to assess whether S1PRs play a role in demyelination induced by lysolecithin (LPC). The data demonstrated that FTY720 and SEW2871 (a S1P1R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
77
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 34 publications
(63 reference statements)
13
77
0
Order By: Relevance
“…5A). In agreement with our previous studies (Pritchard et al, 2014;Sheridan and Dev, 2012), pFTY720 attenuated LPC-induced demyelination compared with control, as observed by expression of myelin oligodendrocyte glycoprotein (MOG) (Fig. 5B) and myelin basic protein (MBP) (Fig.…”
Section: Psychosine Potentiates Lipopolysaccharide (Lps)-induced Levesupporting
confidence: 92%
See 3 more Smart Citations
“…5A). In agreement with our previous studies (Pritchard et al, 2014;Sheridan and Dev, 2012), pFTY720 attenuated LPC-induced demyelination compared with control, as observed by expression of myelin oligodendrocyte glycoprotein (MOG) (Fig. 5B) and myelin basic protein (MBP) (Fig.…”
Section: Psychosine Potentiates Lipopolysaccharide (Lps)-induced Levesupporting
confidence: 92%
“…pFTY720 promotes remyelination as well as limiting the demyelination induced by the bioactive lipid lysolecithin (lysophosphatidylcholine, LPC) (Miron et al, 2010;Sheridan and Dev, 2012). With this in mind, we first determined whether psychosine induced demyelination in cerebellar slices and secondly examined whether pFTY720 attenuated this psychosine-induced demyelination.…”
Section: Psychosine Potentiates Lipopolysaccharide (Lps)-induced Levementioning
confidence: 99%
See 2 more Smart Citations
“…28,[46][47][48] Furthermore, it has also been shown that FTY720 can enhance remyelination in organotypic slice cultures. 27,49,50 In vivo studies demonstrated that FTY720 is effective at treating acute EAE by promoting OPC proliferation and differentiation and by stimulating the sonic hedgehog (Shh) signaling pathway. 51 These results, together with our findings, indicate that FTY720 has both anti-inflammatory and neuroregenerative effects.…”
Section: Discussionmentioning
confidence: 99%